The Effect Of Independence On Auditor Performance (Empirical Study at Inspektorat Daerah Kabupaten Sumedang) - Rahman, Erpi; Nur'aila, Tami (Journal of Business, Accounting and Finance, 2024)
This study aims to determine the effect of independence on auditor performance in Inspektorat Daerah Kabupaten Sumedang. This research uses quantitative methods. Received Aug the number of samples used in this study was 20 respondents. The analysis used is a simple linear regression analysis. The program used to process the required data is Accepted to use the SPSS 26.0 program. The required data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is simple linear regression, correlation coefficient analysis, analysis of the coefficient of determination and t test. The results showed that independence had a positive and significant effect on auditor performance due to tcount > ttable, 2,259 > 2,101 which means Ha was accepted and Ho was rejected. The magnitude of the influence of independence on auditor performance is 22.1% and 87.9% is influenced by other factors